2008
DOI: 10.1111/j.1467-7652.2008.00348.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent protein fusions to a human immunodeficiency virus monoclonal antibody reveal its intracellular transport through the plant endomembrane system

Abstract: SummaryIn order to further understand the production and intracellular trafficking of pharmaceutical proteins in plants, the light and heavy chains (LC and HC) of the human immunodeficiency virus neutralizing monoclonal antibody 2G12 were fused to fluorescent proteins [Venus and monomeric red fluorescent protein (mRFP)] to enable the visualization of their passage through the plant cell. Co-expression of LC and HC with various markers of the endomembrane system demonstrated that LC fusions were found in mobile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…In plants, little is known about the impact of FP fusions. Fusions of monomeric RFP and yellow Venus fluorescent protein to mAb 2G12 were not able to reach the apoplast but being retained in prevacuolar compartments (Irons et al ., ). At difference of such observations, we showed that the mAb14D9‐RFP fusions sorted to the assigned final destinations.…”
Section: Discussionmentioning
confidence: 97%
“…In plants, little is known about the impact of FP fusions. Fusions of monomeric RFP and yellow Venus fluorescent protein to mAb 2G12 were not able to reach the apoplast but being retained in prevacuolar compartments (Irons et al ., ). At difference of such observations, we showed that the mAb14D9‐RFP fusions sorted to the assigned final destinations.…”
Section: Discussionmentioning
confidence: 97%
“…Subcellular localization of antibodies in plants have been studied in a few cases and with various materials (De Wilde et al 1996;During et al 1990), making it difficult to draw a general conclusion. Using reporter fluorescent proteins fused to the light and heavy chains, Irons et al (2008) showed that an antibody transiently expressed in tobacco leaf epidermal cells is located in punctuate structures in close association with the ER and partly overlapping with a pre-vacuolar compartment marker. Whether these punctuate structures correspond to those observed with LO-BM2 expressed in tobacco plants will require a more detailed investigation using various markers of the secretory pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of a broad acting cocktail of protease inhibitors at high concentration had little effect on the IgG fragment pattern for MAb 2G12. These findings suggest that degradation of MAb 2G12 is not related to the process of extraction, more likely, degradation occurs before extraction, and either along the secretory pathway, in the apoplastic space, or in subcellular storage compartments [ 28 ]. These observations support the findings of Hassan et al [ 29 ] who showed little benefit from using protease inhibitors during the extraction of a murine IgG 1 κ at neutral pH to prevent the loss of functional MAb.…”
Section: Discussionmentioning
confidence: 99%